Site Suitability Analysis of Temporary Waste Storage in Desa Popalia Following the Development of USN Kolaka Campus - Putri, Sarnita; Yuyun; Fajar, Wahida; Paisa; Wulandhany, Serly; Firka; Sasmita, Anggit; Sari, Jayanti Yusmah (Majalah Pengabdian Indonesia, 2025)
Desa Popalia, Kecamatan Tanggetada, Kabupaten Kolaka, has experienced an increase in solid waste generation due to the growth of educational activities, migrant settlements, and local economic development following the establishment of the second campus of Universitas Sembilanbelas November (USN) Kolaka. This condition has not been adequately supported by proper waste management facilities, particularly temporary waste storage site (Tempat Penampungan Sementara/TPS), which may lead to environmental and public health problems. This Community Service Program (PKM) aimed to analyze and recommend a suitable location for a TPS based on the environmental and social characteristics of Desa Popalia. The methods included field surveys, primary and secondary data collection, and site suitability analysis using a scoring approach based on environmental, technical-operational, social, and spatial criteria. The results indicate that one alternative location achieved the highest suitability score, as it met key criteria such as safe distance from residential areas, accessibility for waste transportation vehicles, land availability, and community acceptance. This PKM activity provides a technical recommendation for the village government in planning waste management infrastructure. The results are expected to support the development of a more structured, sustainable, and environmentally friendly village waste management system.